2022
DOI: 10.3390/nu14235116
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Behaviors and BMI Stratified by Sex and the ALDH2 rs671 Polymorphism in Japanese Adults

Abstract: The rs671 polymorphism, unique to East Asians, is well known to change the sensitivity to alcohol. Moreover, this polymorphism is associated not only with alcohol intake but also with several dietary behaviors (DBs), chronic diseases, and BMI, but the triadic association among the rs671 genotype, DBs, and BMI is unclear. This study included 12,271 Japanese subjects and aimed to observe this three-way association using the rs671 polymorphism, data of 56 DBs, and BMI. All analyses were stratified by participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Currently, there is no meta-analysis discussing the relationship between ALDH2 and BMI, and our meta-analysis demonstrated that ALDH2 GG populations had a significantly higher BMI than GA/AA populations in the outcome of all subgroups. Some clinical articles have reported lower BMI due to healthier dietary habits caused by flushing syndrome in the GA/AA population ( 68 , 69 ). Besides, it should be clarified that the correlation between ALDH2 and BMI varies among different genders.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no meta-analysis discussing the relationship between ALDH2 and BMI, and our meta-analysis demonstrated that ALDH2 GG populations had a significantly higher BMI than GA/AA populations in the outcome of all subgroups. Some clinical articles have reported lower BMI due to healthier dietary habits caused by flushing syndrome in the GA/AA population ( 68 , 69 ). Besides, it should be clarified that the correlation between ALDH2 and BMI varies among different genders.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the result of the current study, the effect of rs671 is expected to be greater but not robust enough to be found in GWAS, where adjustment for covariates is limited. Based on previous study findings, rs671 is expected to influence several COVID-19-related traits, such as food preference and underlying metabolic conditions and diseases [ 39 41 ], resulting in the inclusion of various noises.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, habitual drinking in ALDH2*2 carriers is a great risk for alcohol-related cancers, such as esophageal cancer, because accumulated acetaldehyde is highly carcinogenic [20,[22][23][24][25]. Nevertheless, drinking habits of ALDH2*2 carriers may have been more easily overlooked by medical professionals, because indicators of overdrinking such as serum liver transaminase levels, blood pressure, serum triglyceride levels, and visceral fat content, are reported to be lower in ALDH2*2 carriers [20,[26][27][28][29][30][31][32][33][34][35][36] even with consideration of drinking amount [26,28,35,36]. The mechanisms underlying this favorable, but enigmatic traits in ALDH2*2 carriers have not been revealed; however, the accumulation of aldehydes is a primary possible reason, considering the role of ALDH2.…”
Section: Introductionmentioning
confidence: 99%